Intrahepatic Cholestasis of Pregnancy - Jurk, Stanisław M.; Kremer, Andreas E.; Schleussner, Ekkehard (Geburtshilfe und Frauenheilkunde, 2021)
Intrahepatic cholestasis of pregnancy (ICP) is a rare but potentially serious complication of pregnancy, the main symptom of which is intense pruritus with elevated serum levels of bile acids. The elevated serum bile acid concentration is regarded as a predictor for poor perinatal outcome including intrauterine death. Ursodeoxycholic acid (UDCA) has become established as the treatment of choice in clinical management to achieve a significant improvement in symptoms and reduce the cholestasis. Pregnant women with severe intrahepatic cholestasis should always be managed in a perinatal centre with close interdisciplinary monitoring and treatment involving perinatologists and hepatologists to minimise the markedly increased perinatal morbidity and mortality as well as maternal symptoms.Die intrahepatische Schwangerschaftscholestase (ICP) ist eine seltene, aber potenziell schwerwiegende Schwangerschaftskomplikation, deren Leitsymptom ein die schwangere Frau quälender Pruritus bei erhöhten Serumspiegeln der Gallensäuren ist. Erhöhte Serumkonzentration gilt als Prädiktor für ein schlechtes perinatales Outcome bis hin zum intrauterinen Tod. Als Therapie der Wahl hat sich Ursodesoxycholsäure (UDCA) zur signifikanten Symptomverbesserung und Verminderung der Cholestase in der klinischen Versorgung etabliert. Die engmaschige Überwachung und Behandlung von Schwangeren mit einer schweren intrahepatischen Cholestase sollte immer in einem Perinatalzentrum interdisziplinär durch Perinatologen und Hepatologen erfolgen, damit neben den maternalen Beschwerden die wesentlich erhöhte perinatale Morbidität und Mortalität minimiert werden.
Keywords: cholestasis of pregnancy; pruritus; bile acids; antenatal care; induction of labor; fetal death